Effect of Early Corticosteroid Therapy on Oxygenation and ICU Stay in Severe Community-Acquired Pneumonia Treated in the critical care unit - Aun Muhammad, Faheed ul Haque, Abdul Waheed, Saleem Adil, Usman Zeeshan, Muhammad Azhar Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Severe community-acquired pneumonia (CAP) remains a major cause of acuterespiratory failure and prolonged intensive care unit (ICU) admission despite advances in antimicrobial and ventilatory management.